2015
DOI: 10.1292/jvms.14-0582
|View full text |Cite
|
Sign up to set email alerts
|

Combination of serum phosphorylated neurofilament heavy subunit and hyperintensity of intramedullary T2W on magnetic resonance imaging provides better prognostic value of canine thoracolumbar intervertebral disc herniation

Abstract: The aim of this study was to evaluate the prognostic value of concurrent measurement of serum phosphorylated neurofilament heavy subunit (pNF-H) concentration and intramedullary T2W hyperintensity in paraplegic to paraplegic dogs. Our hypothesis was that concurrent measurement of these would provide a more accurate prediction of functional outcome in dogs with thoracolumbar intervertebral disc herniation (IVDH). A prospective case-control clinical study was designed using 94 dogs with acute onset of thoracolum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…However, we were not able to detect a difference in serum pNF‐H across groups at baseline, representing the initial 24 hours after injury. While these findings are consistent with a previous study, 15 they are in contrast to earlier reports that found a correlation between serum pNF‐H concentration at the time of hospital admission and functional outcome 13,14 . In particular, serum pNF‐H concentrations at the time of admission observed in these studies ranged from 0 to 60.4 ng/mL in PMM cases, which is markedly higher than values obtained in this study (0‐2.51 ng/mL).…”
Section: Discussionsupporting
confidence: 87%
See 4 more Smart Citations
“…However, we were not able to detect a difference in serum pNF‐H across groups at baseline, representing the initial 24 hours after injury. While these findings are consistent with a previous study, 15 they are in contrast to earlier reports that found a correlation between serum pNF‐H concentration at the time of hospital admission and functional outcome 13,14 . In particular, serum pNF‐H concentrations at the time of admission observed in these studies ranged from 0 to 60.4 ng/mL in PMM cases, which is markedly higher than values obtained in this study (0‐2.51 ng/mL).…”
Section: Discussionsupporting
confidence: 87%
“…Specifically, the predictive value of serum pNF‐H concentration of identifying dogs that recover vs dogs that do not after IVDH has been inconsistent across studies, which might be a reflection of the variability in the time of evaluation relative to injury 13‐15 . Moreover, while previous studies have commented that dogs with PMM have elevated serum pNF‐H concentrations relative to other study cohorts, this particular study sample has neither been specifically evaluated as an individual study cohort, nor serially monitored in the acute postoperative period 13‐15 …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations